Malignant effusions secondary to metastatic thyroid carcinomas: A review of 15 cases. Issue 2 (11th October 2022) - Mustafa, Mohamed Amin; Malenie, Renuka; Mir, Fatima; Hamadeh, Fatima; Policarpio‐Nicolas, Maria Luisa
Abstract: Background: Malignant effusions secondary to thyroid carcinomas are rare, and publications on this topic are limited. This study presents a large cohort of thyroid carcinomas involving effusion cytology. Methods: A 20‐year computerized search for fluid cytology diagnosed with thyroid malignancy was performed. The following data were collected: patients' demographics, clinical findings, and histologic diagnoses. The cytology slides and ancillary tests were reviewed. Results: Among 47, 593 specimens, 15 thyroid carcinomas involving the pleural fluid from 11 patients were found. There were six males and five females with a mean age of 72 years. Ten patients with available follow‐up died of their disease. Papillary thyroid carcinoma (PTC) was the only histologic type. Ten cytology cases were available for review. The cytologic findings common to all cases were nonspecific (clusters/three‐dimensional architecture, enlarged irregular nuclei, and scant to abundant to vacuolated cytoplasm). The classic PTC features were not present in all cases (fine/powdery chromatin [80%], micronucleoli [70%], nuclear grooves [50%], papillary‐like architecture [40%], psammoma bodies [40%], and pseudo‐nuclear inclusions [20%; present on the cell block only]). In 11 of the 15 cases, the diagnosis was rendered with immunohistochemical stains performed on the cell block (paired box 8, thyroid transcription factor 1, and thyroglobulin). In four of the 15 cases, the cytologic diagnosis was made after a comparison with prior surgical pathology or fluid cytology. Conclusions: PTC is the most common histologic type of thyroid malignancy involving pleural effusion. Because the cytologic findings are nonspecific and classic PTC features are not always present, the clinical history in conjunction with immunohistochemical stains is helpful in arriving at the correct diagnosis. Abstract : Thyroid malignancy in effusions is rare and often involves the pleural fluid. Papillary thyroid carcinoma (PTC) is the most common histologic type. The cytologic findings are nonspecific, and classic PTC features are not always present. Immunohistochemical stains are helpful in arriving at the correct diagnosis.